2021
DOI: 10.3390/pharmaceutics13020242
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of pH Dynamics Suppresses Proliferation and Potentiates Doxorubicin Cytotoxicity in Breast Cancer Cells

Abstract: The reverse pH gradient is a major feature associated with cancer cell reprogrammed metabolism. This phenotype is supported by increased activity of pH regulators like ATPases, carbonic anhydrases (CAs), monocarboxylate transporters (MCTs) and sodium–proton exchangers (NHEs) that induce an acidic tumor microenvironment, responsible for the cancer acid-resistant phenotype. In this work, we analyzed the expression of these pH regulators and explored their inhibition in breast cancer cells as a strategy to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…By contrast, we focused on the compounds used in the low micromolar range and evaluated their behavior in coadministration with classical chemotherapeutic drugs. Indeed, some hCA XII inhibitors also restored chemotherapeutic drug efficacy by controlling the pHi values, as for instance acetazolamide. , Also, the activity of P-gp is deeply influenced by pHi, being higher at a slightly alkaline pH . These findings are in line with our observation, showing a higher V max , corresponding to a higher catalytic activity, in HT29/DOX and A549/DOX cells that have higher pHi than their sensitive counterpart, caused by the increased expression of hCA XII .…”
Section: Resultssupporting
confidence: 88%
“…By contrast, we focused on the compounds used in the low micromolar range and evaluated their behavior in coadministration with classical chemotherapeutic drugs. Indeed, some hCA XII inhibitors also restored chemotherapeutic drug efficacy by controlling the pHi values, as for instance acetazolamide. , Also, the activity of P-gp is deeply influenced by pHi, being higher at a slightly alkaline pH . These findings are in line with our observation, showing a higher V max , corresponding to a higher catalytic activity, in HT29/DOX and A549/DOX cells that have higher pHi than their sensitive counterpart, caused by the increased expression of hCA XII .…”
Section: Resultssupporting
confidence: 88%
“…Numerous studies have confirmed that the acidic tumor microenvironment is highly correlated with chemotherapy sensitivity. The acidic tumor microenvironment is maintained by the regulation of pH regulators like ATPases, carbonic anhydrases (CAs), monocarboxylate transporters (MCTs) and sodium–proton exchangers (NHEs), which are responsible for the cancer acid-resistant phenotype . The disruption of the balance of the tumor acidic microenvironment could effectively inhibit the activity of the previously described pH regulators, thereby inhibiting the tumor cell proliferation and increasing the sensitivity of chemotherapy, , which may be the potential mechanism of the synergistic antitumor effect of sodium bicarbonate and doxorubicin.…”
Section: Results and Discussionmentioning
confidence: 99%
“…NHE1 inhibition with cariporide reversed imatinib resistance in BCR-ABL-expressing leukemia cells [ 98 - 100 ] , and NHE1 knockdown sensitized malignant cells to cisplatin-induced apoptosis [ 101 ] . Inhibiting proton extruders, among them NHE1, increased doxorubicin’s cytotoxic effects on breast cancer cell lines [ 102 ] .…”
Section: Proof Of Concept Of the Ph–mdr Relationshipmentioning
confidence: 99%